HAZARD OF DESERTIFICATION AT IBITIPOCA REGION, SOUTHEAST OF MINAS GERAIS STATE, BRAZIL - Fillipe Tamiozzo Pereira Torres; Sarah Lawall; Geraldo César Rocha (Sociedade & Natureza)
The high risk of desertification in Brazil reaches 16% of its territory, including 1482 municipalities only at the semi arid environment (Ministry of Environment, 2005). In terms of human beings, it means almost 32 millions of people, that represents 18% of the brazilian population. The areas already impacted sum 181000 km2 , and the economical impact reaches US$800 million/year.But it is not only at the brazilian semi arid region, located at the northeast part of the country, that the risk of desertification exists.It is well known the desertification problem at the Rio Grande do Sul state, a region with temperate climate, notably in the municipality of Alegrete, in a place called Deserto de São João ( BRASIL, 1994; SOUTO, 1984) Several causes may be listed as responsible for the process, since the climatic pattern, passing by overgrazing and soil salinization, until the natural fragile characteristics and use of thephysical substrate.The Ibitipoca Region, located southeast of Minas Gerais state, in Brazil, is composed basically by thick grained, not cemented and faulted quartzite rocks (figure1). The weathering process has broken this geological material, predominantly composed of quartz, creating acoarse sandy sediment that forms several deposits in the region. The sparse vegetation and the inadequate use of the land has created several hot spots of desertification in the region. Once removed the vegetation, the erosion takes place and magnifies the affected area, menacing the surroundings.